The role of EBUS‐TBNA and standard bronchoscopic modalities in the diagnosis of sarcoidosis. (26th May 2015) - Dziedzic, Dariusz Adam; Peryt, Adam; Orlowski, Tadeusz
Abstract: Background and Aims: Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) is an accurate and minimally invasive technique that has been shown to have excellent diagnostic yield in the diagnosis of mediastinal and hilar lymphadenopathy. However, endoscopic bronchial biopsy (EBB) and transbronchial lung biopsy (TBLB) are still the standard method for making a pathologic diagnosis of sarcoidosis. The aim of this study was to compare the diagnostic yield of EBUS‐TBNA and TBLB through a flexible bronchoscope in patients with stage I and II sarcoidosis. Methods: A total of 653 patients with suspected stage I and II sarcoidosis were included in this retrospective study. After radiological assessment, patients were qualified to bronchoscopy. Patients underwent sequential EBUS‐TBNA followed by TBLB and/or EBB. In all patients, 1056 biopsies from mediastinal lymph nodes group were taken. Results: In all of the biopsied lymph nodes, positive results were obtained in 549 patients (84%). In 180 patients with stage II TBLB, a biopsy was taken from affected part of the lung. Positive results were found in 79 patients (43.9%). EBB was performed in 340 patients, with a positive result in 101 (29.7%). Mediastinoscopy was performed in 60 patients (9.2%) with a negative result in EBUS‐TBNA, TBLB and/or EBB. Non‐caseating granulomas were found in 48 patients. The sensitivity of TBLB technique alone was significantly lower at 43.9% (79/180) ( P  < 0.001). The sensitivity of EBB was significantly lower than EBUS‐TBNA and TBLB and reached 29.7% (101/340) ( P  < 0.0001, P  < 0.003). The overall diagnostic accuracy for EBUS‐TBNA was 84%, and the combination of EBUS‐TBNA with standard bronchoscopic techniques had a diagnostic accuracy of 89%. Conclusion: The diagnostic yield of the EBUS‐TBNA for stage I and II sarcoidosis is clearly higher than for TBLB and EBB. The combination of EBUS‐TBNA with standard bronchoscopic techniques is safe and feasible, and optimizes the diagnostic yield in patients with pulmonary sarcoidosis and enlarged intrathoracic lymph nodes. EBUS‐TBNA in combination with standard bronchoscopy may be considered to be the first‐line investigation in patients with suspected sarcoidosis and enlarged intrathoracic lymphadenopathy.